A review of the prescribing culture of anti-depressants across government districts in Northern Ireland - Mark W. Ruddock; Mark W. Ruddock; Joanne Watt; Mary Jo Kurth; John V. Lamont; Laura Mooney; Peter Fitzgerald (Frontiers Media S.A., 2023)
Introduction: The COVID-19 pandemic has caused a significant increase in mental health issues which general practitioners are now witnessing and managing in communities across Northern Ireland. Unfortunately, this new tsunami of patients with mental health issues has put tremendous strain on our already overburdened health system. As a result, Northern Ireland currently holds the unenviable record for prescribing more anti-anxiety and anti-depressant medication than any other country in the world.Methods: Data was obtained from the Northern Ireland Statistics and Research Agency (NISRA), Family Practitioner Services, General Pharmaceutical Services, Annual Statistics 2020/2021 (published June 2021) and 2021/2022 (published June 2022). Data was analysed by age, gender, district, and socioeconomic class on prescription medication [according to the British National Formulary (BNF)].Results: From 2020/2021 to 2021/2022, the prescribing culture for anti-anxiety and/or anti-depressant medication in Northern Ireland did not abate (24% vs. 14%, female to male, respectively). The postcode and index of multiple deprivation (IMD) was analysed and a mean IMD for each constituency was taken as an estimate of the overall IMD to establish if money spent per patient was related to the IMD in each constituency. North Down, South Antrim, and East Antrim were least deprived, as indicated by their high IMD. Whereas, Foyle, and Belfast West were most deprived (low IMD). The cost of mood and anxiety medication per patient was compared against constituency; patients in Belfast West and Belfast North, followed by Foyle, had the highest costs per patient, and the lowest IMD (most deprived).Conclusion: This review concludes that there has been no change in the prescribing culture for anti-anxiety or anti-depressants across Northern Ireland (2020-2022). The cost of mood and anxiety medication per patient did not correlate with the index of multiple deprivation (IMD). Areas of low IMD trended to have higher spend. Is it now time to review the prescribing culture in Northern Ireland and offer greater support to our GPs to initiate a program of deprescribing and manage the wellbeing of our citizens?